Reconstructing Santri Learning Orientation in the Transformation of Modern Pesantren Education at Pondok Pesantren Bustanul Ulum Jember - Siti Nur Hasanah; Mukni'ah Mukni'ah; Abdul Halim Soebahar; Moch. Imam Machfudi (IJIE International Journal of Islamic Education, 2026)
This study examines the transformation of santri learning orientations within the integration of pesantren, formal schooling, and higher education at Pondok Pesantren Bustanul Ulum Jember. Using a qualitative descriptive approach, data were collected through interviews, observations, focus group discussions, and document analysis involving kyai, administrators, and three santri typologies: Santri Kitab, Santri Siswa, and Mahasantri. The findings show that educational integration in the pesantren does not fully produce epistemological coherence. Instead, it creates differentiated learning orientations, uneven intellectual trajectories, and tensions between traditional religious learning and modern academic demands. Santri kitab tends to maintain text-centered religious authority, students experience academic overload within dual educational systems, while mahasantri face identity ambivalence between pesantren values and contemporary academic culture. This study introduces the concept of hybrid-fragmented learning orientationto explain how integration and fragmentation coexist within modern pesantren education. The study argues that pesantren transformation involves not only institutional modernization but also the negotiation of knowledge, authority, and santri identity. These findings contribute to contemporary Islamic education studies by offering a critical perspective on the complexities of educational integration in modern pesantren education.